Receiving and serving team efficiency in volleyball in relation to team rotation - Laios, A.; Kountouris, P. (International Journal of Performance Analysis in Sport, 2011)
The aim of the present study is to examine whether receiving and serving team efficiency in Volleyball was dependent on the teams' line-up that emerges from the clockwise rotation of the players. The sample comprised all the games of the A1 division of the men's Greek Championship of Volleyball for the 2005-2006 period. Specifically all the points (N=21469) of the two rounds of the regular season from 484 sets in 132 games were taken into account. Receiving team efficiency for the twelve teams ranged from 72.1% to 56.5%. Results showed that the teams' rankings are strongly dependent both on their serving and receiving efficiency (Spearman's rank correlation rho=0.930 and 0.923 respectively). Rotations differ with regards to the teams' serving efficiency (chi-square, p<0.05) but not with regards to their receiving efficiency (chi-square, p=0.08). Most of the teams have one favoured starting line-up position for the set with the setter at zone 1 when serving first and at zone 2 when receiving first. All teams utilized a maximum of two preferred starting line-ups. The decision of the coaches for the starting line-up positions is mostly driven by considerations based on the serving but not the receiving efficiency.